Instrumented cervical fusion using patient specific end-plate conforming interbody devices with a micro-porous structure in nine dogs with disk-associated cervical spondylomyelopathy - Driver, Colin J.; Lopez, Victor; Walton, Ben; Jones, Dan; Fentem, Rory; Tomlinson, Andrew; Rose, Jeremy (Frontiers in Veterinary Science, 2023)
Objective To report the medium and long-term outcome of nine dogs with disk-associated cervical spondylomyelopathy (DA-CSM), treated by instrumented interbody fusion using patient specific end-plate conforming device that features a micro-porous structure to facilitate bone in-growth. Study design A retrospective clinical study. Animals Nine medium and large breed dogs. Methods Medical records at two institutions were reviewed between January 2020 and 2023. Following magnetic resonance imaging (MRI) diagnosis of DA-CSM, pre-operative computed tomography (CT) scans were exported to computer software for in-silico surgical planning. Interbody devices were 3D-manufactured by selecting laser melting in titanium alloy. These were surgically implanted at 13 segments alongside mono-or bi-cortical vertebral stabilization systems. Follow-up included neurologic scoring and CT scans post-operative, at medium-term follow up and at long-term follow-up where possible. Interbody fusion and implant subsidence were evaluated from follow-up CT scans. Results Nine dogs were diagnosed with DA-CSM between C5-C7 at a total of 13 operated segments. Medium-term follow up was obtained between 2 and 8 months post-operative (3.00 ± 1.82 months). Neurologic scoring improved (p = 0.009) in eight of nine dogs. Distraction was significant (p < 0.001) at all segments. Fusion was evident at 12/13 segments. Subsidence was evident at 3/13 operated segments but was only considered clinically relevant in one dog that did not improve; as clinical signs were mild, revision surgery was not recommended. Long-term follow up was obtained between 9 and 33 months (14.23 ± 8.24 months); improvement was sustained in 8 dogs. The dog that suffered worsened thoracic limb paresis at medium-term follow up was also diagnosed with immune-mediated polyarthropathy (IMPA) and was euthanased 9 months post-operative due to unacceptable side-effects of corticosteroid therapy. Conclusion End-plate conforming interbody devices with a micro-porous structure were designed, manufactured, and successfully implanted in dog with DA-CSM. This resulted in CT-determined fusion with minimal subsidence in the majority of operated segments. Clinical significance The technique described can be used to distract and fuse cervical vertebrae in dogs with DA-CSM, with favorable medium-and long-term outcomes.